Analisis Efektivitas Regimen Terapi Antiretroviral terhadap Status Viral Load pada Pasien HIV di Puskesmas Umbulharjo 1 dan Gedongtengen: Effectiveness Analysis of Antiretroviral Therapy Regimens on Viral Load Status Among HIV Patients at Umbulharjo 1 and Gedongtengen Community Health Centers - Prita Anggraini Kartika Sari; Risa Widiastuti; Nida Amalia Azmi (Universitas Ngudi Waluyo, 2025)
Human Immunodeficiency Virus (HIV) remains a major public health challenge, including in the Special Region of Yogyakarta. This study compares the effectiveness of two first-line antiretroviral therapy (ART) regimens, namely TLD (Tenofovir-Lamivudine-Dolutegravir) and TLE (Tenofovir-Lamivudine-Efavirenz), in reducing viral load among HIV patients at two community health centers. A retrospective cohort design using convenience sampling was conducted based on medical records from Gedongtengen Community Health Center (January 2021–June 2023) and Umbulharjo 1 Community Health Center (January 2021–December 2022). Inclusion criteria comprised adult patients (≥17 years) who received TLD or TLE for at least six months and had complete viral load data. Statistical analyses (chi-square test, odds ratio) were performed on 102 patients (mean age 28.94 ± 9.98 years; 90.2% male). The majority (96.1%) were in early stages (1–2) of HIV infection, and 6.9% had opportunistic infections. Viral load suppression was achieved in 52% of patients receiving TLD compared to 21% in the TLE group (p = 0.015; OR = 3.01). The superior efficacy of TLD is attributed to Dolutegravir’s mechanism as an integrase inhibitor with a high barrier to resistance. Despite some limitations, these findings support prioritizing TLD as the preferred first-line ART regimen, particularly for patients in early stages of HIV infection. ABSTRAK Human Immunodeficiency Virus (HIV) menjadi tantangan utama kesehatan masyarakat, termasuk di Daerah Istimewa Yogyakarta. Penelitian ini membandingkan efektivitas dua regimen terapi antiretroviral (ART) lini pertama, yaitu TLD (Tenofovir-Lamivudine-Dolutegravir) dan TLE (Tenofovir-Lamivudine-Efavirenz) dalam menurunkan viral load pasien HIV di dua puskesmas. Metode yang digunakan yaitu kohort retrospektif dengan convenience sampling dilakukan pada rekam medis di Puskesmas Gedongtengen (Januari 2021–Juni 2023) dan Puskesmas Umbulharjo 1 (Januari 2021–Desember 2022). Kriteria inklusi meliputi pasien dewasa (≥17 tahun) yang menerima TLD/TLE minimal selama 6 bulan dan memiliki data viral load lengkap. Analisis statistik (chi-square, odds ratio) dilakukan pada 102 pasien (rerata usia 28,94 ± 9,98 tahun; 90,2% laki-laki). Sebanyak 96,1% berada pada stadium awal (1–2) dan 6,9% mengalami infeksi oportunistik. Penekanan viral load tercapai pada 52% pasien penerima TLD, dibandingkan 21% pada TLE (p = 0,015; OR = 3,01). Keunggulan TLD diduga disebabkan oleh mekanisme Dolutegravir sebagai penghambat integrase dengan high resistance barrier. Meskipun memiliki keterbatasan, temuan ini mendukung prioritas TLD sebagai regimen ART lini pertama, khususnya bagi pasien stadium awal HIV.